2011
DOI: 10.1126/science.1204132
|View full text |Cite
|
Sign up to set email alerts
|

The 2010 M w 8.8 Maule Megathrust Earthquake of Central Chile, Monitored by GPS

Abstract: Large earthquakes produce crustal deformation that can be quantified by geodetic measurements, allowing for the determination of the slip distribution on the fault. We used data from Global Positioning System (GPS) networks in Central Chile to infer the static deformation and the kinematics of the 2010 moment magnitude (M(w)) 8.8 Maule megathrust earthquake. From elastic modeling, we found a total rupture length of ~500 kilometers where slip (up to 15 meters) concentrated on two main asperities situated on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
364
3
8

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 368 publications
(404 citation statements)
references
References 26 publications
29
364
3
8
Order By: Relevance
“…However, south of 35.5 • S the slip of still a significant number of events exceeds the afterslip from the GPS in a region where largely aftershocks related to the plate interface were located (Lange et al 2012). Agurto et al (2012) compared the seismic slip of the first 12 d with the TA model from Vigny et al (2011) and similarly found regions where the slip from seismicity exceeds the TA model. As the TA on the plate interface must be inferred from observations of surface displacements the TA model is severely limited in spatial resolution (Hetland & Simons 2010), particularly offshore, and effectively averages small slip patches like those caused by moderate and even strong events over larger regions.…”
Section: Methods 1: Relating Css To Ta and The Different Spatial Resolmentioning
confidence: 99%
See 2 more Smart Citations
“…However, south of 35.5 • S the slip of still a significant number of events exceeds the afterslip from the GPS in a region where largely aftershocks related to the plate interface were located (Lange et al 2012). Agurto et al (2012) compared the seismic slip of the first 12 d with the TA model from Vigny et al (2011) and similarly found regions where the slip from seismicity exceeds the TA model. As the TA on the plate interface must be inferred from observations of surface displacements the TA model is severely limited in spatial resolution (Hetland & Simons 2010), particularly offshore, and effectively averages small slip patches like those caused by moderate and even strong events over larger regions.…”
Section: Methods 1: Relating Css To Ta and The Different Spatial Resolmentioning
confidence: 99%
“…3) and by its location between the two co-seismic slip maxima of the Maule 2010 event (e.g. Vigny et al 2011).…”
Section: Methods 2: Calculation Of Afterslip To Aftershocks Ratio (Asar)mentioning
confidence: 99%
See 1 more Smart Citation
“…2011. Tais plataformas possibilitam igualmente o tratamento de aspectos relacionados com a recuperação das principais características da distribuição de deformações e falhamentos VIGNY et al, 2011;DELOUIS et al, 2010). No entanto, tais ferramentas limitam-se a aspectos morfológicos de natureza geométrica e/ou relativa.…”
Section: Introductionunclassified
“…The epicenter of the main shock was located approximately 100 km to the north of the station offshore in the Maule region in central Chile. The epicenter of the smaller earthquake that occurred 90 min after the main shock was approximately 200 km southwest of the observation station (Figure 2) [Vigny et al, 2011;Bedford et al, 2013].…”
Section: Application To Gnss Seismologymentioning
confidence: 99%